The role of mural mechanics on cephalopod palaeoecology. Issue 164 (25th March 2020) - Lemanis, Robert; Stier, Deborah; Zlotnikov, Igor; Zaslansky, Paul; Fuchs, Dirk
Abstract : Cephalopods transformed the molluscan shell into a buoyancy device that must be strong enough to resist external water pressure. Historically, unique features of the shell have been interpreted on the basis that the strength of the shell presents a hard limit on maximum habitat depth. One such feature is the mural flap, which is a semi-prismatic layer deposited on the inner surface of some coleoid septa that has been suggested to strengthen the shell and permit colonization of deeper waters. We test this hypothesis by constructing finite-element models that show how mural modifications affect the response of the shell to hydrostatic pressure. The mural flaps are found to have no notable structural function. Another mural modification discovered here is the adapical ridge flap that initially seemed to have a potential function in shifting peak stress away from the attachment site of the septum; however, the irregular distribution of this feature casts any functional interpretation in doubt. Ecological separation of belemnites and decabrachians is likely not mediated by the presence/absence of mural flaps. This work illustrates a potential caveat that not all unique septal features formed in response to increasing hydrostatic pressure and deeper habitats.